Intergenerational Transmission of Unemployment - Evidence for German Sons - Miriam Mäder; Steffen Müller; Regina T. Riphahn; Caroline Schwientek (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies the association between the unemployment experience of fathers and their sons. Based on German survey data that cover the last decades we find significant positive correlations. Using instrumental variables estimation and the Gottschalk (1996) method we investigate to what extent fathers' unemployment is causal for offsprings' employment outcomes. In agreement with most of the small international literature we do not find a positive causal effect for intergenerational unemployment transmission. This outcome is robust to alternative data structures and to tests at the intensive and extensive margin of unemployment.
Keywords: J62; C21; C26; 330; youth unemployment; non-employment; intergenerational mobility; causal effect; Gottschalk method